Analisis Yuridis Terhadap Penanganan Pelaku Penyimpangan Seksual Eksibisionisme Melalui Sanksi Rehabilitasi Mental dan Pemidanaan - Anisa R. Sunge; Fence M. Wantu; Vifi Swarianata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Exhibitionism is the behavior of showing body parts or vital organs to others to achieve sexual satisfaction. This is done to get sexual satisfaction by masturbating while imagining. Exhibitionism itself is included in the category of sexual preference disorder (paraphilia). This research aims to analyze whether the application of mental rehabilitation sanctions can be carried out against the perpetrators of exhibitionism. The type of research used is normative research which is based on applicable laws and regulations and analyzes problems from a case perspective. The results of the research obtained by the author in conducting research on the application of mental rehabilitation sanctions have the potential to reduce the level of recurrence of exhibitionism behavior. Mental rehabilitation programs that include psychological therapy, counseling, and social support can help offenders to understand the root causes of their behavior and develop strategies to overcome these tendencies.